THE PEMAKAIAN LUMBAL KORSET PADA INTERVENSI MICRO WAVE DIATHERMY, TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION, ULTRA SOUND MENGURANGI NYERI SPONDILOSIS LUMBALIS. - Sujana, I Gede (Majalah Ilmiah Fisioterapi Indonesia, 2013)
Low back pain in spondylosis lumbalis condition caused by a decrease in disc space and the narrowing of the intervertebral foramen. And a decrease in disc space narrowing of the intervertebral foramen can produce irritation of the nerve roots causing back pain is spreading. The purpose of this study was to determine how much to increase the effectiveness of pain reduction on a combination of lumbar corset giving MWD, TENS and US. Experimental studies have been done with the design of randomized pre test and post test group design. Sample size of 28 is divided into two groups of 14 persons each. Group I with a combination of MWD, TENS, and the U.S., whereas group II  treatment with MWD, TENS, U.S. and lumbar corset. The data was collected by measuring the intensity of pain using the VAS, at the time before and after treatment, then performed with different test t test (paired t test and independent t test). The results showed significant effect of each treatment to decrease pain intensity p = 0.000 (p <0.05). But the average level of pain after treatment II treatment seems more effective to reduce pain. The use of lumbar corset in patients with spondylosis lumbalis will serve to control the pain as it can restrict movement or lumbar support. So it is advisable to add a lumbar corset on a combination of giving MWD, TENS and U.S. to reduce pain in patients with spondylosis lumbalis.
Keywords: Lumbar Corset, MWD, TENS and U.S., Pain, Spondylosis Lumbalis